2019
DOI: 10.1136/bcr-2019-231260
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent immune thrombocytopenia following different vaccines

Abstract: A boy developed immune thrombocytopenia 2 weeks after receiving his measles-mumps-rubella and varicella vaccines at 12 months of age. He then had a recurrent episode 1 week after the booster doses of his quadrivalent diphtheria-tetanus-pertussis-polio, pneumococcal and meningococcal group C vaccines at 5 years of age. On both the occasions he required hospitalisation and treatment with intravenous immunoglobulin. He received other vaccines, before and in between, without any adverse events. Future vaccines are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
1
1
Order By: Relevance
“…After two years of follow-up, none of the children in the vaccine-associated thrombocytopenia subgroup experienced an ITP relapse following re-immunization, while three children with persistent or chronic ITP in the vaccine-unassociated thrombocytopenia subgroup experienced an ITP relapse. Although a few case reports documented recurrent ITP following the same or different vaccinations [ 31 , 32 ], our findings demonstrated that revaccination for children with prior ITP and the administration of the incident vaccine and other vaccines to children with previous vaccine-associated thrombocytopenia did not result in the recurrence or progression of thrombocytopenia. Moreover, the prognosis was usually favorable for children who suffered an episode of vaccine-associated thrombocytopenia.…”
Section: Discussioncontrasting
confidence: 60%
“…After two years of follow-up, none of the children in the vaccine-associated thrombocytopenia subgroup experienced an ITP relapse following re-immunization, while three children with persistent or chronic ITP in the vaccine-unassociated thrombocytopenia subgroup experienced an ITP relapse. Although a few case reports documented recurrent ITP following the same or different vaccinations [ 31 , 32 ], our findings demonstrated that revaccination for children with prior ITP and the administration of the incident vaccine and other vaccines to children with previous vaccine-associated thrombocytopenia did not result in the recurrence or progression of thrombocytopenia. Moreover, the prognosis was usually favorable for children who suffered an episode of vaccine-associated thrombocytopenia.…”
Section: Discussioncontrasting
confidence: 60%
“…The concept of immunization-induced thrombocytopenia is not new, nor is unusual at young age. Namely, ITP, either de novo or a relapse of ITP has been reported to be associated with various vaccines, including measles-mumps-rubella (MMR), Haemophilus influenzae, diphtheria-tetanus-pertussis (DTP), polio and hepatitis B virus, with similar pathogenesis as in COVID-19 mRNA vaccine [23][24][25][26][27]. It is presumed that de novo ITP might be associated with molecular mimicry and circulating immune complexes, and that an ITP relapse is the result of preformed antibodies [28].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed reactions include [4]: cytotoxic reactions (type II), i.e. thrombocytopenia after administration of the measles-rubella vaccine [15][16][17]; reactions mediated by immune complexes (type III), i.e. serum sickness [18][19][20], Arthus reaction [21-22], erythema nodosum [23][24] or Henoch-…”
Section: Classification Of the Adverse Reactions To Vaccinesmentioning
confidence: 99%
“…Injection site reactions include two major patterns: a) pain, redness, and/or swelling and b) persistent subcutaneous itchy nodules at the injection site [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Their frequency depends on the composition of the vaccine, the number of injections previously administered, and the immunological and inflammatory responses of the host [30,31].…”
Section: Injection Site Reactions To Vaccinesmentioning
confidence: 99%